The Impact of Chatbots and Virtual Assistants in Medical Education and Clinical Decision-Making - Bhadresh C Koladiya; Yukt Bhagiya; Jisan Yunusbhai Jadav; Prashant V Kariya (Medical Science: Recent Advances and Applications Vol. 3, 2025)
The integration of chatbots and virtual assistants in medical education and clinical decision-making has revolutionised the healthcare landscape. These AI-driven tools enhance learning experiences by providing interactive, personalised education to medical students and professionals. In clinical settings, they support decision-making by offering real-time, evidence-based recommendations, reducing diagnostic errors, and improving workflow efficiency. This review explores the applications, benefits, and challenges of chatbots and virtual assistants in medical education and clinical decision-making. It also examines their potential to bridge knowledge gaps, improve patient outcomes, and augment healthcare delivery. While these technologies offer significant advantages, concerns related to data security, accuracy, and ethical implications must be addressed for their optimal implementation.